The satisfaction of students who are about to graduate from research projects Field study on a sample of students at Dr. Tahar Moulay Saida University - KOURATK, karima; senouci, boumediene (Journal of Social Sciences and Humanities, 2024)
The Study aims to know the level of satisfaction of scientific research topics university’ s license student’s, at university Dr Tahar Moulay , Saida, and if there are any different between those students attributable to their gender and specialization. The study included (76) student they were chosen intentionally, in order to measure their satisfaction, and we used (14) questions, and the researchers use the descriptive method appropriate for this study, after analyses we find this following result: - The level of scientific research topics university’ s license student’s is low -. There are statistically significant differences in the level of satisfaction included to the variable of gender - There are statistically significant differences in the level of satisfaction included to the variable of specialization.